Disponibilidade dos metais cobre e chumbo em um canal de maré receptor de efluentes de carcinicultura - Torres, Roseline Freire (2009)
In the Jaguaribe´s river estuary is located the largest area of shrimp farming in the state of Ceará occupying 1,316 ha pond, about 50% of entire shrimp farming activity of the state. The concern about heavy metals contamination through of the shrimp farming activities requires a several studies with the purpose of measuring the impacts of wastewater in receivers systems and particularly the incorporation into the biota. Availability of heavy metals copper (Cu) and lead (Pb) in Cumbe´s channel that receiver wastewater from the main area of shrimp farming acticity in the region was determined through the use of biomonitors and selective extractionmethod. The Cu showed percentages ranging from 36.8 to 58.3% in the weakly fraction bound to sediment. The concentrations of Cu ranged from 1.27 to 2.55 (1.59 ± 0.48) (μg/g) in algae (Ulva lactuca), 18.1 to 22.8 (μg/g) (20, 9 ± 1.6) in the shrimp muscle tissue and from 54.2 to 54.5 (μg / g) (54.4 ± 0.2) in the shrimp exoesqueleton (Litopenaeus schimitti), 10.6 to 17.1 (μg/g) (13.8 ± 3.7) in the crabs muscle tissue and from 53.2 to 57.9 (μg / g) (55.5 ± 3.3) in the crabs exoesqueleton (Callinectes sapidus) of 4, 6 to 12.0 (μg/g) (7.6 ± 2.3) in oysters (Crassostrea rhizophorae) and from 11.2 to 19.9 (μg/g) (15.6 ± 3.0) in mussel (Mytella falcata). Lead showed no detectable concentrations in both organisms, in the weakly fraction bound to sediment and the SSM in the Cumbe´s channel in opposite, showed high percentuals in the available form in the Pacoti´s channel. The increase in the concentracions of lead may have reflecting the fate of be situated next to urban area. The concentrations of Cu in MPS ranged from 12.6 to 28.9 (μg/g) (18.1 ± 5.6) about two times throughout the channel the highest values near the exit region of the effluent carninicultura of being transported to the adjacent estuarine region. The sedimentary profiles analyzed showed that a recent increase in the concentrations of Cu in the superficial layers. The results showed that the highest concentrations of this element are associated with the fine size grain of sediments and the increase in the organic matter levels from the shrimp farming.